Ecocide in Avatar: The Way of Water (2022) - An Ecocritical Approach - Andrianto, Mohammad Yoga (Universitas Negeri Surabaya, 2024)
Environmental damage, driven by global warming and rapid climate change, is one of Earth's most urgent issues. The rise in global temperatures has resulted in severe weather events, threatening ecosystems, biodiversity, and human health. This destruction, termed ecocide, was first introduced by Arthur W. Galston in 1970 and later expanded by environmental lawyer Polly Higgins. Ecocide refers to extensive damage to ecosystems, often leading to significant harm to local populations and biodiversity. This paper explores ecocide through historical and contemporary lenses, detailing Galston's efforts against the use of Agent Orange in Vietnam and Higgins' campaign to recognize ecocide as an international crime. It also examines real-world examples of ecocide, including the deforestation of the Amazon Rainforest, the destruction of the Aral Sea, and pollution of the Citarum River, highlighting human activities' detrimental impacts on the environment. Additionally, the paper analyzes the depiction of ecocide in James Cameron's film Avatar: The Way of Water (2022), which portrays the catastrophic consequences of environmental destruction through deforestation, illegal hunting, and the overexploitation of resources. The film serves as a reflection of real-world issues, emphasizing the themes of human greed, ignorance, and the dire state of Earth. This analysis underscores the importance of understanding and addressing ecocide to protect biodiversity and ensure a sustainable future for the planet.